SMRT sequencing of the Campylobacter coli BfR-CA-9557 genome sequence reveals unique methylation motifs. (December 2015) - Zautner, Andreas; Goldschmidt, Anne-Marie; Thürmer, Andrea; Schuldes, Jörg; Bader, Oliver; Lugert, Raimond; Groß, Uwe; Stingl, Kerstin; Salinas, Gabriela; Lingner, Thomas
Abstract Background Campylobacter species are the most prevalent bacterial pathogen causing acute enteritis worldwide. In contrast toCampylobacter jejuni, about 5 % ofCampylobacter coli strains exhibit susceptibility to restriction endonuclease digestion byDpn I cutting specifically 5'-Gm ATC-3' motifs. This indicates significant differences in DNA methylation between both microbial species. The goal of the study was to analyze the methylome of aC. coli strain susceptible toDpn I digestion, to identify its methylation motifs and restriction modification systems (RM-systems), and compare them to related organisms likeC. jejuni andHelicobacter pylori . Results Using one SMRT cell and the PacBio RS sequencing technology followed by PacBio Modification and Motif Analysis the complete genome of theDpn I susceptible strainC. coli BfR-CA-9557 was sequenced to 500-fold coverage and assembled into a single contig of 1.7 Mbp. The genome contains a CJIE1-like element prophage and is phylogenetically closer toC. coli clade 1 isolates than clade 3. 45, 881 6-methylated adenines (ca. 2.7 % of genome positions) that are predominantly arranged in eight different methylation motifs and 1, 788 4-methylated cytosines (ca. 0.1 %) have been detected. Only two of these motifs correspond to known restriction modification motifs. Characteristic for this methylome was the very high fraction of methylation of motifs with mostly above 99 %. Conclusions Only five dominant methylation motifs have been identified inC. jejuni, which have been associated with known RM-systems.C. coli BFR-CA-9557 shares one (RAATTY) of these, but four ORFs could be assigned to putative Type I RM-systems, seven ORFs to Type II RM-systems and three ORFs to Type IV RM-systems. In accordance withDpn I prescreening RM-system IIP, methylation of GATC motifs was detected inC. coli BfR-CA-9557. A homologous IIP RM-system has been described forH. pylori . The remaining methylation motifs are specific forC. coli BfR-CA-9557 and have been neither detected inC. jejuni nor inH. pylori . The results of this study give us new insights into epigenetics of Campylobacteraceae and provide the groundwork to resolve the function of RM-systems inC. coli .